Ampelopsin targets in cellular processes of cancer: Recent trends and advances. (2022) - Tuli, Hardeep Singh; Sak, Katrin; Garg, Vivek Kumar; Kumar, Ajay; Adhikary, Shubham; Kaur, Ginpreet; Parashar, Nidarshana Chaturvedi; Parashar, Gaurav; Mukherjee, Tapan Kumar; Sharma, Uttam; Jain, Aklank; Mohapatra, Ranjan K.; et al.
Abstract: Cancer is being considered as a serious threat to human health globally due to limited availability and efficacy of therapeutics. In addition, existing chemotherapeutic drugs possess a diverse range of toxic side effects. Therefore, more research is welcomed to investigate the chemo-preventive action of plant-based metabolites. Ampelopsin (dihydromyricetin) is one among the biologically active plant-based chemicals with promising anti-cancer actions. It modulates the expression of various cellular molecules that are involved in cancer progressions. For instance, ampelopsin enhances the expression of apoptosis inducing proteins. It regulates the expression of angiogenic and metastatic proteins to inhibit tumor growth. Expression of inflammatory markers has also been found to be suppressed by ampelopsin in cancer cells. The present review article describes various anti-tumor cellular targets of ampelopsin at a single podium which will help the researchers to understand mechanistic insight of this phytochemical. Graphical Abstract: ga1